Control of Ice-Ice Disease and Growth in Farming Red Algae Kappaphycus alvarezii (Doty) Doty through the Application of Diversification Method - Tisera, Wilson Lodewyk (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2024)
The farming of red algae Kappaphycus alvarezii (trade name Eucheuma cottonii) has grown rapidly in East Nusa Tenggara since 1999, which has contributed significantly to increasing the income of the communities and region. The biggest problem faced since a decade ago is the ice-ice disease phenomenon which attacks the farming of K. alvarezii, reducing production, and the farmer's income drastically. This experimental study aimed to minimize the ice-ice disease infestation in the farming of K. alvarezii through the application of diversification methods. This research was conducted in the farming area of K. alvarezii in Sulamu Waters from July-September 2020. An experimental method was tested in order to minimize ice-ce disease infestation. As a treatment, three longline nylon ropes were used with three replicates. The first line was placed by Gracilaria sp seeds; the second line by K. alvarezii seeds; while the third line by Sargassum polycystum seeds. The conventional farming method carried out by local farmers was used as control. The parameters tested were disease incidence and intensity as well as growth rate. The result showed that both treatment and control showed infestation of ice-ice disease. Farming with treatment using Gracilaria sp. and Sargassum polycistum gave better resistance to ice-ice disease compared to the one without (control). The treatment showed less incidence (12-38%), and intensity (0.05-0.435) of ice-ice disease compared to the control, 30-45% and 2,1-17,19% respectively. The contrary happened related to the growth rate. The control showed better daily growth (mean 4.74%) compared to the treatment (mean 4.70%).